2017
DOI: 10.1002/cbdv.201700028
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity, Phenolic Constituents and Toxicity of Hot Water Extract from Red Maple Buds

Abstract: The present study reports, for the first time, the results of the antioxidant capacity and the phenolic composition of a hot water extract from red maple buds (RMB), as well as its safety. In this regard and comparatively to antioxidant standards, this extract exhibits a significant antiradical capacity when tested by 2,2-diphenyl-1-picrylhydrazyl (DPPH ) and anion superoxide trapping assays. High-resolution mass spectrometric and nuclear magnetic resonance analyses permitted to determine for the first time, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 40 publications
(69 reference statements)
0
19
0
Order By: Relevance
“…These compounds were identified to be maplexin A (retention time, t R = 7.768 min; Peak 1), Ginallin 3,6 ( t R = 10.118 min, Peak 4), Maplexin D ( t R = 10.426 min, Peak 5), and Ginnalin A ( t R = 11.887, min Peak 7). Previous studies have also reported the presence of these four phenolic compounds in the hot water extract of red maple bark and buds (Geoffroy, Meda, et al, ; N. R. Meda et al, ).…”
Section: Resultsmentioning
confidence: 82%
“…These compounds were identified to be maplexin A (retention time, t R = 7.768 min; Peak 1), Ginallin 3,6 ( t R = 10.118 min, Peak 4), Maplexin D ( t R = 10.426 min, Peak 5), and Ginnalin A ( t R = 11.887, min Peak 7). Previous studies have also reported the presence of these four phenolic compounds in the hot water extract of red maple bark and buds (Geoffroy, Meda, et al, ; N. R. Meda et al, ).…”
Section: Resultsmentioning
confidence: 82%
“…Compounds 51 and 53 were further tentatively identified as quercetin‐3‐ O ‐galloyl hexosides by their high‐intensity radical aglycone ion at m/z 300 in MS/MS spectra. Notably, a quercetin‐ O ‐galloyl‐hexoside was previously reported in the red maple species .…”
Section: Resultsmentioning
confidence: 85%
“…Compound 64 ( t R = 31.90 min) displayed a deprotonated ion at m/z 433 and was tentatively identified as quercetin‐3‐ O ‐pentoside based on the characteristic fragment ions of quercetin at m/z 301, 255, and 151, the diagnostic daughter ion of 3‐OH substituted quercetin at m/z 300, and the loss of 132 Da corresponding to a pentose moiety. Notably, quercetin‐3‐ O ‐arabinoside has previously been reported from the red maple species .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations